Genesis And Evolution Of Corruption - Khidirov Khoshim Ibodullaevich; Fayzullaeva Klara Abdullaevna (Genius Journals, 2022)
This article covers issues such as the origin of corruption, its genesis, stages of development and evolution.
Keywords: Lagash city-state; Uruinimgina; corruption; genesis